Structural Properties and Antifungal Activity against Candida albicans Biofilm of Different Composite Layers Based on Ag/Zn Doped Hydroxyapatite-Polydimethylsiloxanes - Groza, Andreea (Polymers (Basel), 2016)
Modern medicine is still struggling to find new and more effective methods for fighting off viruses, bacteria and fungi. Among the most dangerous and at times life-threatening fungi is Candida albicans. Our work is focused on surface and structural characterization of hydroxyapatite, silver doped hydroxyapatite and zinc doped hydroxyapatite deposited on a titanium substrate previously coated with polydimethylsiloxane (HAp-PDMS, Ag:HAp-PDMS, Zn:HAp-PDMS) by different techniques: Scanning Electron Microscopy (SEM), Glow Discharge Optical Emission Spectroscopy (GDOES) and Fourier Transform Infrared Spectroscopy (FTIR). The morphological studies revealed that the use of the PDMS polymer as an interlayer improves the quality of the coatings. The structural characterizations of the thin films revealed the basic constituents of both apatitic and PDMS structure. In addition, the GD depth profiles indicated the formation of a composite material as well as the successful embedding of the HAp, Zn:HAp and Ag:HAp into the polymer. On the other hand, in vitro evaluation of the antifungal properties of Ag:HAp-PDMS and Zn:HAp-PDMS demonstrated the fungicidal effects of Ag:HAp-PDMS and the potential antifungal effect of Zn:HAp-PDMS composite layers against C. albicans biofilm. The results acquired in this research complete previous research on the potential use of new complex materials produced by nanotechnology in biomedicine.